Penerapan PERMA Nomor 1 Tahun 2020 Dalam Perkara Tindak Pidana Korupsi : (Studi Kasus Putusan Nomor 33/Pid.Sus/TPK/2020/PN.Pdg) - Divani Fajria Hadi; Efren Nova (Fakultas Hukum Universitas Andalas, 2023)
Based on data from Indonesia Corruption Watch, in the last 4 years corruption cases related to state’s financial losses are the most committed and increase significantly, oftentimes have disparities in punishment. To overcome this, PERMA No. 1 of 2020 concerning Article 2 and Article 3 of the Corruption Eradication Law was issued. The interesting thing is even though there is a guideline for sentencing related offenses, there are still court decisions that are not in accordance with the provisions of PERMA. One of them is Decision No. 33/Pid.Sus/TPK/2020/PN.Pdg. The issues that are tried to be discussed are: 1) How is the application of PERMA No. 1 of 2020 in Decision No. 33/Pid.Sus/TPK/2020/PN.Pdg; and 2) What is the basis for the judge's consideration in sentencing the defendant in Decision No. 33/Pid.Sus/TPK/2020/PN.Pdg. This research uses normative juridical methods through case approach and statue approach. The results show that: 1) The application of PERMA No. 1 of 2020 in Decision No. 33/Pid.Sus/TPK/2020/PN.Pdg, has not been perfectly applied by the panel of judges. In sentencing, the judge is less thorough so that the crime imposed on the defendant is lower than the level of guilt; and 2) The basis for the judge's consideration in sentencing the defendant in Decision No. 33/Pid.Sus/TPK/2020/PN.Pdg, considers the role of the defendant who, although as the driving force or mastermind of this crime, the defendant will not be able to carry it out if there is no cooperation with the authorized person. Therefore, the panel of judges imposed a lower sentence than the Prosecutor’s demand.